Structure and Floristic Composition of Oak (Quercus semecarpifolia SM.) Forest at Domje Chauki, Rasuwa District, Central Nepal - Subedi, M. N.; Shakya, P. R. (Indian Forester, 1993)
Natural oak (Quercus semecarpifolia Sm.) forest at Domje Chauki, Rasuwa District, Central Nepal was studied in a sample plot of 1600 m2 at an altitude of 2840 m. Structure, floristic composition, tree density, diameter distribution and basal area percentage were studied. Need to conserve the broadleaved forests bas been stressed.